Analisis Pengaruh Indepedensi, Task Complexity, dan Kompetensi Auditor Terhadap Kualitas Audit - Annisa Nurbaiti; Erlangga Prakasa (Politeknik Ganesha Medan, 2022)
Financial statements have two characteristics, namely reliable and relevant which are difficult to measure so that users of this information need the services of an auditor who has good audit quality. This study aims to determine and analyze the effect of variable independency, task complexity, and auditor competency on audit quality at the Public Accounting Firm in Denpasar City simultaneously and partially. The sample used is the auditor at the Public Accounting Firm in Denpasar City which is 45 people in total. The primary data that has been obtained is then processed using the IBM SPSS version 23 application and tested using multiple linear regression, F- test, and t-test. Based on the result of the study, it was found that the three factors, namely independency, task complexity, and auditor competency have a simultaneous effect on audit quality at the Public Accounting Firm in Denpasar, Bali. For partial result, the independency and competency variables have a positive and significant effect on audit quality, while the task complexity variable has a negative and significant effect on audit quality. It is expected that this research can be an additional information for further research, for the company management as consideration in choosing audit services, and for the Public Accounting Firm as evaluation to improve audit quality.